Using Coal as a Pressure Instrument - Fita , Daniel Nicolae; Obretenova , Mila Ilieva; Stanila , Sorina Daniela; Zamora , Adriana; Eugen , Safta Gheorghe; Grecu-Muresan , Florin (Advances and Challenges in Science and Technology Vol. 3, 2023)
Coal is a solid carbon-rich substance that is generally brown or black and occurs in layered sedimentary strata. It is one of the most significant major fossil fuels. Coal continues to be an important source of energy that can maintain its role as a safe fuel, for many countries it is the only fuel available to meet the growing electricity demand needed to raise living standards and standards of living. The development of energy energy around the globe, as characterized by the scarcity of finite main energy resources (oil, natural gas, coal, and uranium) and/or electrical power to final consumers, as well as the desire of the world's major energy powers to own and control the entire global energy chain for the purpose of using primary energy resources or electricity as a possible energy weapon or pressure instrument in the context of blackmail and profitability, makes this paper extremely important. Lack of supply of primary energy resources or electricity to final consumers causes societal crises with possible military escalation and can cause States of societal imbalance, causing extreme damage to citizen safety, industry, national economy, and, implicitly, national security. In this setting, a state's energy security becomes a crucial pillar of national, regional, and global security, giving consumers safety, stability, and well-being but also being a source of civil and/or armed conflict. The use of coal, which is a strategic primary energy resource as a possible energy weapon or instrument of pressure, is closely linked to the exercise of energy and economic power, an important component in a state’s power complex. The lack of energy infrastructures of some less developed energy and economic States has led to increased games on their side and allowed some "energy monopolies" in terms of control of re(sources) and energy lines of markets and prices for primary energy resources. In this context, energy security is no longer just some economic policy objective, but has become a solid and constant concern for the global energy Community.